Plywood Production Development Strategy at CV Alaf Denida - Alfina Taswirul Fanni (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
CV Alaf Denida is a local wood-processing company located in Babat, Lamongan, East Java. CV Alaf Denida started their business in 2013 focused on fabrication in processing of sengon (albasia) into bare core as main material for blockboard production. The factory located in Desa Dradah Blumbang. Kecamatan Kedungpring, Kabupaten Lamongan. This research aims to make a design production development strategies at CV Alaf Denida by identifying internal and external factor of the company, analyzing alternative strategies of production development and recommending priority strategies which is used by CV Alaf Denida in developing the products. The research metode is a qualitative method with an intrinsic case study approach. The collecting data method used in this research done with observasion process, interview, and documentation. Analysis tools used for analyzing the data are IFE, EFE, SWOT, and QSPM matrix for showing the priority strategies. The validity test of this research using researcher triangulation, method, and resource data.